2015
DOI: 10.1007/s00253-015-6739-2
|View full text |Cite
|
Sign up to set email alerts
|

Molecular methods for studying methanogens of the human gastrointestinal tract: current status and future directions

Abstract: Until recently, human gut microbiota was believed to be colonized by few methanogenic archaeal species. Much higher microbial diversity within the human gut was revealed by the use of molecular approaches as compared to routine microbiological techniques, but still, a lot remains unknown. Molecular techniques has the advantage of being rapid, reproducible, and can be highly discriminative as compared to conventional culturing methods. Some of them provide both qualitative and quantitative information. However,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
4
2
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 130 publications
(142 reference statements)
1
9
0
Order By: Relevance
“…Production of CH 4 using H 2 is restricted to Archaea, with the order Methanobacteriales containing Methanobrevibacter smithii and Methanosphaera stadtmanae as the dominant methanogens in human beings. 42,43 Evidence has emerged suggesting that CH 4 is linked to constipation, 44 and it has been reported that M smithii is found more commonly in patients with IBS-C. 45 In our study, 33% of study subjects harbored detectable levels of Methanobacteriales, with no difference between healthy subjects and IBS patients. Interestingly, there was a significant correlation between exhaled CH 4 and the detection of Methanobacteriales by quantitative PCR, which is in line with previous findings.…”
Section: Discussionsupporting
confidence: 44%
“…Production of CH 4 using H 2 is restricted to Archaea, with the order Methanobacteriales containing Methanobrevibacter smithii and Methanosphaera stadtmanae as the dominant methanogens in human beings. 42,43 Evidence has emerged suggesting that CH 4 is linked to constipation, 44 and it has been reported that M smithii is found more commonly in patients with IBS-C. 45 In our study, 33% of study subjects harbored detectable levels of Methanobacteriales, with no difference between healthy subjects and IBS patients. Interestingly, there was a significant correlation between exhaled CH 4 and the detection of Methanobacteriales by quantitative PCR, which is in line with previous findings.…”
Section: Discussionsupporting
confidence: 44%
“…Moreover, the clinical interest on archaea is minor, due to the fact that there are no known or proved archaeal pathogens yet (Gill et al, 2006). Nevertheless, (methanogenic) archaea are part of the commensal microorganisms inhabiting the human body, being regularly detected in the oral cavity and the gastrointestinal tract (Chaudhary et al, 2015;Gaci et al, 2014;Horz and Conrads, 2011;Nkamga et al, 2017); in the latter they sometimes even outnumber the most abundant bacterial species (14%, (Tyakht et al, 2013);). Most human archaea studies use either cultivation or qPCR methods (Grine et al, 2017;Koskinen et al, 2017;van de Pol et al, 2017;Wampach et al, 2017) and only a few, 16S rRNA gene-based archaeacentric studies are available Moissl-Eichinger et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…This sample was chosen as it tested positive for all the usual types of methanogens that may be encountered in the human gut [14], i.e. the species Methanobrevibacter smithii ( Mb.…”
Section: Methodsmentioning
confidence: 99%